TRADISI PERKAWINAN ALEK JAMU DI LINGKUNGAN ADAT NAGARI LUBUAK BATINGKOK DALAM PERSPEKTIF HUKUM ISLAM - M Al Fadhli; Eficandra Eficandra (Institut Agama Islam Negeri Batusangkar, 2022)
In Islam, the validity of a marriage occurs when the marriage contract has fulfilled the pillars and conditions. If the pillars and conditions are fulfilled, then the marriage can be done this because there is no longer a barrier to realizing a marriage. However, in Nagari Lubuak Batingkok, Lima Puluh Kota Regency, there is a tradition before holding a marriage called the alek herbal tradition where this tradition is a series that must be taken before carrying out a marriage and carrying out walimahtul ursy activities. If the traditional procession is not carried out, the marriage cannot be carried out because it will cause someone to be prevented from getting married. If the marriage continues, the bride's family will be subject to customary sanctions in the form of not being brought again in traditional activities in the village. This research focuses on the implementation of the alek jamu marriage tradition, the impact and consequences of the alek jamu marriage tradition and how the alek jamu marriage tradition in the traditional environment of Nagari Lubuak Batingkok, Harau District, 50 City Regency according to the Islamic Law Perspective. The type of research carried out is field research which is processed descriptively. The results of this study indicate that in the implementation of this traditional herbal medicine, the traditional processions carried out are Manalisiak, manyuduik and ayam putiah tabang Siang. The impact of not carrying out this traditional herbal medicine is the obstruction of marriage, banishment as long as it is customary, paying fines, being ostracized in the community and becoming a disgrace and mental pressure for the family in the community. The traditional tradition of alek jamu marriage in Nagari Lubuak Batingkok according to the perspective of Islamic law is allowed because it is categorized as Urf sahih due to the element of benefit in its implementation, namely to get a good partner and establish closeness with niniak mamak. However, if the alek jamu tradition contains harm in the form of preventing marriage and causing elopement, then this tradition is not allowed because it is categorized as urf fasid.